Magnetic Ligand Fishing Using Immobilized Cyclooxygenase-2 for Identification and Screening of Anticoronary Heart Disease Ligands From Choerospondias axillaris - Chi, Miaomiao; Wang, Hongsen; Yan, Zhankuan; Cao, Lei; Gao, Xun; Qin, Kunming (Frontiers in Nutrition, 2022)
Inhibition of cyclooxygenase-2（COX-2）activity is an effective way for treatment of coronary heart disease. And as an important source of COX-2 inhibitors, Choerospondias Axillaris’s bioactive compounds and pharmacological mechanisms remained lacking of prospective researches. Therefore, for the purpose of accelerating discovery of natural products targeting designed inhibitors, the COX-2 microreactor composed of functionalized microspheres and magnetic ligand fishing was developed and applied in Choerospondias Axillaris, and the physicochemical properties of the COX-2 functionalized microspheres were characterized using Fourier transform infrared spectroscopy (FT-IR), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Furthermore, the bioactive compounds singled out from ethanol decoction without pre-purification were dissociated and identified by ultra-performance liquid chromatography plus Q-Exactive Orbitrap tandem mass spectrometry (UPLC-Q-Exactive orbitrap-MS/MS). Consequently, 21 bioactive compounds consisting of 6 organic acids, 8 flavonoids, and 7 others were separated and characterized from Choerospondias Axillaris, which were reported to participate in the COX-2 inhibitory pathway to varying degrees. Therefore, this method could provide prospective solution for the extraction and identification of active pharmaceutical ingredients and the rapid screening of some enzyme inhibitors in complex mixtures.